Assessment for apraxia in Mild Cognitive Impairment and Alzheimer's disease - Mirela Ward; Juliana F. Cecato; Ivan Aprahamian; José Eduardo Martinelli (Dementia & Neuropsychologia)
OBJECTIVE: To evaluate apraxia in healthy elderly and in patients diagnosed with Alzheimer's disease (AD) and Mild cognitive impairment (MCI). METHODS: We evaluated 136 subjects with an average age of 75.74 years (minimum 60 years old, maximum 92 years old) and average schooling of 9 years (minimum of 7 and a maximum of 12 years), using the Mini-Mental State examination (MMSE), Cambridge Cognitive Examination (CAMCOG) and the Clock Drawing Test. For the analysis of the presence of apraxia, eight subitems from the CAMCOG were selected: the drawings of the pentagon, spiral, house, clock; and the tasks of putting a piece of paper in an envelope; the correct one hand waiving "Goodbye" movements; paper cutting using scissors; and brushing teeth. RESULTS: Elder controls had an average score of 11.51, compared to MCI (11.13), and AD patients, whose average apraxia test scores were the lowest (10.23). Apraxia scores proved able to differentiate the three groups studied (p=0.001). In addition, a negative correlation was observed between apraxia and MMSE scores. CONCLUSION: We conclude that testing for the presence of apraxia is important in the evaluation of patients with cognitive impairments and may help to differentiate elderly controls, MCI and AD.